EP 59. Multi-modal imaging of neural correlates of motor speed performance in the trail making test. Issue 9 (September 2016) - Camilleri, J.; Reid, A.; Müller, V.; Grefkes, C.; Amunts, K.; Eickhoff, S.
Abstract : The assessment of motor and executive functions following stroke or traumatic brain injury is a key aspect of impairment evaluation and used to guide further therapy. In clinical routine such assessments are largely dominated by pen-and-paper tests. While these provide standardized, reliable and ecologically valid measures of the individual level of functioning, rather little is yet known about their neurobiological underpinnings. Therefore, the aim of this study was to investigate brain regions and their associated networks that are related to upper extremity motor function, as quantified by the Motor Speed subtest of the Trail Making Test (TMT-MS) (Delis et al., 2001 ). Whole brain voxel-based morphometry (Ashburner and Friston, 2000 ) and whole brain tract-based spatial statistics (Smith et al., 2006 ) were used to investigate the association between TMT-MS performance with gray matter volume (GMV) and white matter integrity respectively. While results demonstrated no relationship to local white-matter properties, we found a significant correlation between TMT-MS performance and GMV of the lower bank of the inferior frontal sulcus, a region associated with cognitive processing, as indicated by assessing its functional profile by the BrainMap database (Laird et al., 2011 ). Using this finding as a seed region, we further examined and compared networks as reflected by resting state connectivity (Fox and Raichle, 2007 ), meta-analytic-connectivity modeling (Eickhoff et al., 2011 ), structural covariance (Albaugh et al., 2013 ) and probabilistic tractography (Behrens et al., 2003 ). While differences between the different approaches were observed, all approaches converged on a network comprising regions that overlap with the multiple-demand network. Our data therefore indicates that performance may primarily depend on executive function, thus suggesting that motor speed in a more naturalistic setting should be more associated with executive rather than primary motor function. Moreover, results showed that while there were differences between the approaches, a convergence indicated that common networks can be revealed across highly divergent methods.